KENYAMANAN TERMAL DAN ADAPTASI PERANCANGAN BANGUNAN DI KOTA BALIKPAPAN - Atik Adinda; Reny Rachmawati; Abdul Mattin (Display Architecture Journal, 2022)
The temperature of the earth's surface is changing due to the problem of climate change. Air temperature can affect the level of human comfort in carrying out daily activities. This study aims to assess the thermal comfort of the city of Balikpapan based on the factors of air temperature, humidity and wind speed taken from data for a week. The analytical tool in this study is to use the Predicted Mean Vote (PMV method) to assess the level of the thermal comfort scale based on the American Society of Heating, Refrigerating and Air-conditioning Engineers (ASHRAE) Standard 55-66. 00.00 is Cold with a score (-3), at Cold Score (-3), at 12.00 slightly warm score (1), and at 18.00 a neutral score (0). This requires architectural design through a thermal comfort approach that is able to increase the adaptation of buildings in the city of Balikpapan according to the comfort level of the community.